IMMU-01. Combining CD28 and 4-1BB costimulationin trans enhances the anti-glioma efficacy and persistence of B7-H3 CAR T cells in immune-competent brain tumor models. (3rd June 2022) - Haydar, Dalia; Elayan, Abdul; Yi, Zhongzhen; Gottschalk, Stephen; DeRenzo, Chris; Krenciute, Giedre
Abstract: We and others have demonstrated that B7-H3 CAR T-cells have potent antitumor responses in xenograft models for brain tumors; however, these models do not recapitulate the immunosuppressive tumor microenvironment (TME) in patients with high-grade glioma. To evaluate the safety and efficacy of antigen-specific CAR T-cells, we adapted the immune-competent GL261 glioma model which recapitulates human disease and host immune barriers. We generated a library of B7-H3 CARs with different transmembrane (CD8, CD28), costimulatory (CD28, 4-1BB), and activation (ζ, mutζ) domains. We then compared their cytolytic activity, expansion, and anti-tumor activity. Results show that B7-H3 CARs with CD28 transmembrane and costimulatory domains have superior efficacy compared to CARs with CD8 and 4-1BB domains. Additionally, CARs with mutated ζ activation domain have better overall persistence. However, providing costimulation signals through CD28 or 4-1BB alone does not induce superior anti-glioma efficacy of B7-H3 CAR T-cells in vivo . Thus, we next investigated whether incorporating 4-1BB signaling into CD28-based CARs using in tran s design enhances the therapeutic efficacy of B7-H3 CAR T-cells. We found that in repeat stimulation assays, surface expression of 4-1BBL enhanced expansion of B7H3 CAR T-cells at least 300-folds more than T-cells with CD28 or 4-1BB costimulatory domains alone. Additionally, 4-1BBL expression significantly enhanced the sequential killing capacity compared to CD28- or 41BB-based B7-H3 CAR T-cells. High dimensional flow cytometry analysis of GL261 tumors post CAR T-cell injection revealed unique immune clusters including dendritic cells and lymphoid predominant populations in mice treated with 4-1BBL expressing CARs. Thus, expression of 4-1BBL on CD28-based CARs reshaped the TME and enhanced persistence and anti-glioma efficacy of B7-H3 CAR T-cells. Studies examining transcriptional and epigenetic programs, and TME/CAR T-cell interactions are in progress. Results will define pathways that dictate CAR T-cell performance and will identify unique mechanisms for further improvements utilizing other members of TNF-superfamily.